A new species of Eremobothynus Ohaus (Coleoptera: Scarabaeidae: Dynastinae) from Argentina, with notes on Eremobothynus cornutus (Steinheil) - Grossi, Paschoal Coelho; Abadie, Esteban Ignácio (Zootaxa, 2008)
The genus Eremobothynus Ohaus, 1910 includes two species from Argentina. A synopsis of the genus was provided by Endrödi (1969, 1985) and since his last contribution no new species have been described. In this paper we describe a new third species from Entre Ríos, Argentina. At present, all Eremobothynus species are endemic to Argentina and known from only few localities. Taxonomic notes are given for E. cornutus (Steinheil), leading to the discussion and correction of some diagnostic characters of the genus. Additionally, a key for the identification of the species is provided.